Menata Ulang Patriotisme dan Nasionalisme Indonesia - Subaryana Subaryana (Prodi Pendidikan Sejarah Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Sumatera, 2022)
Nationalism and patriotism must always be developed in the heartstrings of the Indonesian people as a tool to fill independence and at the same time maintain the sovereignty of the nation and state. As the world globalizes, nationalism and patriotism today are not only focused on the domestic level but must be able to counteract foreign intervention in various areas of life, especially those that harm the nation and state. The purpose of this study is to reveal the value of nationalism and patriotism towards the nation and state. This research uses qualitative descriptive method. The data sources used in this study are mostly derived from literature studies. The results showed that the concepts of nationalism and patriotism are dynamic concepts because of dialectics from domestic social, political, economic, and cultural changes as well as changes in the global level. Therefore, nationalism and patriotism need to be reorganized so as not to lead to narrow nationalism (chauvinism) and blind patriotism (djangoism). Nationalism and internationalism cannot be contested but must go hand in hand for the betterment of the nation and the state.